Study on Optimal Parameter and Target for Pulsed-Field Ablation of Atrial Fibrillation - Ye, Xuying; Liu, Shangzhong; Yin, Huijuan; He, Qiang; Xue, Zhixiao; Lu, Chengzhi; Su, Siying (Frontiers in Cardiovascular Medicine, 2021)
Pulsed field ablation (PFA) had potential advantages in atrial fibrillation ablation and we aims to confirm the optimal parameter and target of PFA for atrial fibrillation. Two ablation modes in vitro of single cell system (ablation in electrode cup) and monolayer cell system (ablation in inserts with electrode tips) were established to perform PFA for myocardial cell H9C2(2-1) and smooth muscle cell A7r5. Ablation effect, Calcium ion influx, the expression of CX45 and surface morphological change was observed. Three Bama minipigs were used to verify the in vivo ablation effect of PFA. In monolayer cell system, H9C2(2-1) was significantly sensitive to PFA compared with A7R5, with shrinking of the whole monolayer. The ablation effect of bidirectional pulse was weaker than the two mono-polar pulse. Expressed CX45 proteins were increased in H9C2(2-1) but decreased in A7R5 cells. Bidirectional pulsed PFA performed on Bama minipigs were able to effectively block electrical activity from pulmonary vein to atrium with week muscle contraction, not generating pulmonary vein stenosis. Bidirectional pulsed PFA was able to significantly ablate myocardial cells, maintain cell-cell connection and reduce muscle contraction, which was a kind of optimized PFA ablation strategy for atrial fibrillation.